1936
DOI: 10.1111/j.1746-1561.1936.tb08847.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Normal and Pathological Locomotion in Man

Abstract: PIp. vi+48. 4 text-figs. and 15 plates. Price l0s. 6d. net. This book presents a full and ordered account of the method of dissection of the brain by defibrillation or blunt dissection, and some of the results to be obtained by this method are shown in the many illustrations, almost all of which are photographs of actual specimens.Though the method is not new and has been used in England previously by Jamieson and by Green, as far as we know it has not been set out in book form as a laboratory manual until now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1957
1957
1999
1999

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In spite of the deficiencies in his knowledge of anatomy and physiology he is still considered by many to be the greatest scientific genius the world has ever seen 7 , 8 . In De Motu Animalium (334 BC ), he gave a geometrical analysis of muscular flexion as a change from a straight line, to an angle and he recognized that without flexion there could be no forward progression 9 . In his writings On Parts of Animals and On Progression of Animals , he described the transfer of rotary motion of the feet to translatory motion, and he recognized that, in moving, the animal makes its change of position by pressing against that which is beneath it 10 .…”
Section: The Anatomical Periodmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of the deficiencies in his knowledge of anatomy and physiology he is still considered by many to be the greatest scientific genius the world has ever seen 7 , 8 . In De Motu Animalium (334 BC ), he gave a geometrical analysis of muscular flexion as a change from a straight line, to an angle and he recognized that without flexion there could be no forward progression 9 . In his writings On Parts of Animals and On Progression of Animals , he described the transfer of rotary motion of the feet to translatory motion, and he recognized that, in moving, the animal makes its change of position by pressing against that which is beneath it 10 .…”
Section: The Anatomical Periodmentioning
confidence: 99%
“…He found that when agonists are under reflex stimulation, the excitation of one centre of control is simultaneous with the inhibition of the other. This, together with the all‐or‐none reaction, is fundamental to the understanding of the kinetic events of the human body 9 …”
Section: The Physiological Periodmentioning
confidence: 99%
See 3 more Smart Citations